Comparison between use of fentanyl and rocuronium on outpatient undergoing ultra-short duration gynecologic surgery: a randomized, double-blind, controlled trial - Eun-Su Choi; Kuen Su Lee; Da Som Kang; Yoon Ji Choi; Too Jae Min; Yoon Sook Lee; Jae Hwan Kim; Kyung-Jin Min; Woon Young Kim (IMR Press, 2022)
Background: There has been a steady increase in outpatient-based ultra-short duration gynecology surgeries. However, there are no detailed studies on anesthesia regimens for these surgeries. The aim of this study was to compare the effects of low-dose rocuronium and fentanyl single bolus for their suitability with these patients. Methods: A total of 60 patients were randomly divided into three groups: a control group (group C, n = 20) that received 3 mL of normal saline; a fentanyl group (group F, n = 19) that received 1 mcg/kg of fentanyl; and a low-dose rocuronium group (group R, n = 20) that received 0.3 mg/kg of rocuronium. We collected hemodynamic data during anesthetic induction and the intraoperative period. We also investigated supraglottic airway (SGA) insertion condition, patient's gross movements, and surgeon's satisfaction. In addition, we evaluated the incidence of postoperative nausea and vomiting, pruritus, first voiding time and discharge time from the postanesthetic care unit. Results: Systolic, diastolic, and mean blood pressure were significantly lower in group F after SGA insertion (p = 0.031, p = 0.046 and p = 0.048). SGA insertion conditions scores were significantly worse in group C than in group F and group R for total score (p < 0.001). Also, the number of patient movements during surgery and the number of rescue fentanyl injections were significantly higher in group C than group F and group R (p = 0.005 and p < 0.001). Conclusion: Fentanyl administration at 1 mcg/kg has advantages compared with rocuronium and is a more suitable single agent regimen for outpatient-based ultra-short duration gynecology surgeries.